Representation of Racial Issue in Poetry “Passing Time” by Maya Angelou (Sastra Inggris UNPAM, 2024)
This study discusses the analysis of a poem by American poet Maya Angelou entitled Passing Time. This study aims to determine the effect of racism that occurs in this poem. And this article also aims to remind people about how big the effect of racism is. In this study the authors used a qualitative descriptive methods with the theories of racism by Ali Rattansi. The theories of racism were used with the aim of knowing the effects of racism that occur in real life. These results show types of racism that can be found in the poem such as discriminations, injustice, skin color, segregation, in this poem also found racist acts against black people. This poem tells about someone who has black and white skin color which Angelou describes in this poem as twilight and musk. Angelou tries to suggest that there is no difference between two skin tones/skin tones.